2016
DOI: 10.1108/cpoib-03-2014-0017
|View full text |Cite
|
Sign up to set email alerts
|

Global oligopolistic competition and foreign direct investment

Abstract: The purpose of this paper is to re-visit and re-invigorate the oligopolistic industry perspective on MNC strategy. Based on insights from the Industrial Organization tradition and Strategic Management, the paper brings the original insights of the oligopolistic industry perspective into a modern context by outlining a conceptual framework that may guide future International Business (IB) research on MNC strategy in oligopolistic industries. This paper demonstrates how contemporary IB literature pays little att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 86 publications
(155 reference statements)
0
4
0
Order By: Relevance
“…Along these lines, a motivation for choosing a location was put forward by Knickerbocker (1973) suggesting that firms in oligopolistic markets follow each other's location decisions if they are uncertain about production costs in the host country, and therefore, by following their rivals through 'defensive investments', they reduce risks. It has been shown that firms which compete in domestic markets tend to follow each other to the same foreign markets, while noncompeting firms try to avoid each other geographically when internationalising (Hansen & Hoenen, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, a motivation for choosing a location was put forward by Knickerbocker (1973) suggesting that firms in oligopolistic markets follow each other's location decisions if they are uncertain about production costs in the host country, and therefore, by following their rivals through 'defensive investments', they reduce risks. It has been shown that firms which compete in domestic markets tend to follow each other to the same foreign markets, while noncompeting firms try to avoid each other geographically when internationalising (Hansen & Hoenen, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, the confluence of a large number of foreign MNEs active in various sectors of the host economy may favour local cooperation for innovation. Exclusive clientsupplier relationships are sometimes extended from the home country of these companies into the host country (Hansen, 2016;Rama & Ferguson, 2007). These foreign firms may have built global alliances, whereby cooperation in Spain constitutes only a part of their worldwide linkages.…”
Section: Discussionmentioning
confidence: 99%
“…From a business perspective, managers need to accurately predict the reactions of other firms when making decisions over market entry (Argyres et al, 2019;Hansen & Hoenen, 2016). The output decisions predicted by the Cournot model approximate closely to practical outcomes, even though the decision-making process may seem unconventional, and so the model is eminently suitable for analyzing strategic decision-making in international business.…”
Section: The Cournot Equilibriummentioning
confidence: 99%